Characterizing seasonal groundwater storage in alpine catchments using time‐lapse gravimetry, water stable isotopes and water balance methods. Issue 22 (6th September 2020) - Arnoux, Marie; Halloran, Landon J. S.; Berdat, Eléonore; Hunkeler, Daniel
Abstract: Alpine areas play a major role in water supply in downstream valleys by releasing water during warm and dry periods. However, the hydrogeology of alpine catchments, which are particularly exposed to the effects of climate change, is currently not well understood. Increasing our knowledge of alpine hydrogeological processes is thus of considerable importance for any forward‐looking hydrological investigations in alpine areas. The objectives of this study are to quantify seasonal groundwater storage variations in a small Swiss alpine catchment and to evaluate the capabilities of time‐lapse gravimetry in the identification of zones of high groundwater storage fluctuations. Time‐lapse gravimetric measurements enable rapid localisation of zones of dynamic groundwater storage changes and help to highlight aquifers with a higher storage decrease. Temperature sensors enable measurement of the temporal trend in stream and spring drying in the post‐snowmelt period. Stable isotope measurements allow us to identify the origin of surface water exiting the catchment. The results improve our comprehension of a conceptual schema highlighting two different hydrogeological systems: (a) a shallow, rapidly depleted one fed directly by snowmelt and (b) a deeper one, with a slower recession, fed by main recharge during peak snowmelt and emerging at the lower part of the catchment below the talus and moraine of the catchment where bedrock is exposed. These dynamics confirm the high variability of storage in the talus and moraine aquifers and highlight the dominant role of Quaternary deposits and their connectivity to store water over seasonal and multi‐year time‐scales. The mechanisms explaining the importance of Quaternary deposits are the combination of moraine and talus with different permeabilities allowing the storage of sufficient quantities of water permitting continuous release during drier periods of the year. Abstract : Figure legend: Schematic diagram of the hydrogeological processes during the post‐melt period in a talus and moraine snow‐dominated catchment, typical of the alpine regions.